The Moderating Role of Brand Attachment in the Relationship between Brand Awareness and Brand Engagement on Apparel Purchase Retention on TikTok Shop among Generation Z - Abdul Hadi Hari; Sri Ekanti Sabardini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
This study is conducted in the context of the growing use of social media-based e-commerce platforms, particularly TikTok Shop, by Generation Z for purchasing apparel products. This phenomenon highlights the need to understand the factors influencing consumer loyalty, especially those related to brand awareness, consumer engagement, and emotional attachment to brands. The aim of this research is to analyze the influence of Brand Awareness and Brand Engagement on Purchase Retention, as well as to evaluate the moderating role of Brand Attachment in strengthening these relationships. The study employs a correlational quantitative research design using a survey method. The population consists of Generation Z consumers who have previously purchased apparel products via TikTok Shop. A purposive sampling technique was used, resulting in 150 respondents. Data were analyzed using SmartPLS software to examine both the direct relationships and the moderating effects among variables. The findings reveal that both Brand Awareness and Brand Engagement positively affect Purchase Retention. Moreover, Brand Attachment is proven to moderate these relationships, indicating that emotional attachment to the brand strengthens the influence of brand awareness and engagement on purchase loyalty. This research contributes theoretically by reinforcing the model of relationships among awareness, engagement, attachment, and purchase retention within the context of social media-based e-commerce. Practically, the findings offer valuable insights for marketers in designing strategies to enhance consumer loyalty by increasing awareness, fostering engagement, and building emotional attachment to brands on digital platforms.